Intradural extramedullary spinal cord meningioma with a rare extradural foraminal extension: A case report - Almatrafi, Faisal; Alomair, Majed; Alojan, Abdulrazaq; Alkhaldi, Mohammed; Alsafwani, Noor; Aseeri, Abdullah; Alshahrani, Abdulelah; Alsalmi, Sultan; Alqahtani, Mohammad (Frontiers in Surgery, 2023)
Background Meningiomas are mostly benign and slow-growing neoplasms of the central nervous system. Spinal meningiomas account for up to 45% of all intradural spinal tumors in adults and up to 25%–45% of all spinal tumors. Spinal extradural meningiomas are rare and may be easily confused with malignant neoplasms. Case description A 24-year-old woman was presented to our hospital with paraplegia and loss of sensation in the T7 dermatome and lower body. MRI findings showed T6-T7 right-sided intradural extramedullary and extradural lesion, measuring 1.4 cm × 1.5 cm × 3 cm, extending to the right foramen, compressing the spinal cord, and displacing it to the left. Hyperintense lesion on T2 and hypointense lesion on T1 were observed. The patient reported improvement after surgery and during follow-up. We recommend maximizing the decompression during surgery to achieve better clinical outcome. Extradural meningiomas represent 5% of all meningiomas; therefore, having an intradural on top of extradural meningioma with extraforaminal extensions makes this a unique and rare case. Conclusion Meningiomas can be easily missed in diagnosis depending on imaging and the pathognomonic pattern it represents, which can mimic other pathologies, such as schwannomas. Therefore, surgeons should always suspect their patient having a meningioma even if the pattern is not typical. Moreover, preoperative preparation, such as navigation and defect closure, must be taken in case it turns out be a meningioma instead of the presumed pathology.